Prospek Pengembangan Sarana dan Prasarana sebagai Daya Tarik Wisata Pantai Paal dan Pantai Pulisan - Prayerti Eunike Kondoy; Jolanda Esther Kaihatu; Jelly Robot (Jurnal Social Science, 2023)
Tourism activities require adequate facilities, infrastructure, and accommodation. This study aims to identify aspects of the facilities, infrastructure, and accessibility of Paal Beach and Pelican Beach tourism objects. The research method uses a quantitative, empirical approach. Data collection techniques include observation, questionnaires, documentation, and literature studies. Data analysis with scoring analysis The results of the research show that the condition of facilities and accessibility is quite adequate. Meanwhile, the condition of the infrastructure for Paal Beach and Pelican Beach attractions is in a low category.